2016
DOI: 10.1002/cctc.201600484
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance Base‐Metal Approach for the Oxidative Esterification of 5‐Hydroxymethylfurfural

Abstract: Exploring high‐performance base‐metal approaches for the sustainable production of chemicals from biomass is presently attracting immense interest and is truly important to promote their industrialized application. Herein, CoOx‐N/C and α‐MnO2 were combined as a base‐metal catalyst that can achieve high yields of furan‐2,5‐dimethylcarboxylate (FDMC, 95.6 %) for the catalytic oxidative esterification of 5‐hydroxymethylfurfural (HMF) without basic additive. The reaction proceeds through fast conversion of HMF to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 57 publications
4
44
0
Order By: Relevance
“…Previously, our laboratory has been engaged in research of construction of functional catalytic materials and production of chemicals from biomass‐based feedstocks via catalytic methods . We found that both basic sites (pyridinic N‐doped carbon species in CoO x ‐N/C) and basic supports (MgO and Mg(OH) 2 ) could contribute to high catalytic performances in oxidation or oxidative esterification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, our laboratory has been engaged in research of construction of functional catalytic materials and production of chemicals from biomass‐based feedstocks via catalytic methods . We found that both basic sites (pyridinic N‐doped carbon species in CoO x ‐N/C) and basic supports (MgO and Mg(OH) 2 ) could contribute to high catalytic performances in oxidation or oxidative esterification.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Particularly,b asic pyridinic-N species doped in carbons could remarkably promote for the dehydrogenation steps. [21] Nevertheless, these non-noble metal catalysts generally suffer from low activity when used alone. [22] To improvet he catalytic activity,v ariousb asic additives are introducedi nt he reactions in term of activating substrates or lowering the activation energy of specific steps, [23,24] but the problemscaused by base stillremained.…”
Section: Introductionmentioning
confidence: 99%
“…Other ecofriendly reaction of great interest is the synthesis of acetals and esters from furan derivatives because the increase in the number of carbon atoms makes them potential additives for diesel fuels . It has been recently reported that homogeneous cobalt catalysts containing pyridine ligands exhibit a high performance in the esterification of furan derivatives …”
Section: Introductionmentioning
confidence: 99%
“…A poor yield of FDCA (20 %) was observed at a HMF conversion of 73 % with Au–Pd/ZOC if no NaHCO 3 was added in the reaction system, leading to an unselective reaction pathway. Moreover, the catalyst was deactivated presumable through adsorption of the formed carboxylic intermediates/products and/or humins on the surface of the noble metal particles . If the NaHCO 3 /HMF molar ratio increased to 2, a total conversion of HMF with FDCA yield of 88 % was obtained.…”
Section: Resultsmentioning
confidence: 99%